Integrative Mechanisms Towards Zero Emissions Regional Planning: An Enabler of Regional Development: A Case Study of Europe - Kalogiannidis, Stavros; Kontsas, Stamatis; Syndoukas, Dimitrios; Chatzitheodoridis, Fotios (International Journal of Energy Economics and Policy, 2024)
This study explores the role of integrative mechanisms in facilitating zero emissions regional planning, acting as a catalyst for regional development within Europe. Utilizing a quantitative methodology and questionnaire, data were collected from 384 European regions, followed by rigorous statistical analysis. The findings highlight the significance of effective integrative mechanisms in achieving zero emissions, confirming a positive impact on regional development. The results show that Zero emissions regional planning positively impacts regional development. This study also notes that the presence of identifiable challenges (e.g., financial constraints, policy conflicts, technological gaps) significantly hinders the alignment of regional development objectives with zero-emissions targets. These results have substantial implications for stakeholders, emphasizing the need for a collaborative approach in regional planning and suggesting pathways for future research endeavors. Policymakers should pay particular attention to the challenges identified in the study, such as financial constraints, policy conflicts, technological gaps, and cultural resistance to change. Strategies should be developed to mitigate these challenges, including creating financial mechanisms to support zero-emissions initiatives, harmonizing policies at various levels of governance, investing in technology transfer and innovation, and implementing educational and awareness programs to change cultural attitudes.